2020
DOI: 10.1002/slct.202001657
|View full text |Cite
|
Sign up to set email alerts
|

Screening of α‐Glucosidase Inhibitors from Houttuynia cordata and Evaluation of the Binding Mechanisms

Abstract: α‐glucosidase inhibitors have been used to treat diabetes for many years. Recently, natural products have attracted much attention, because they are kinds of safety source to screen α‐glucosidase inhibitor. In this study, we separated two monomers (quercitrin and afzelin) from Houttuynia cordata with notable inhibitory activity against α‐glucosidase, and evaluated inhibitory kinetics and the binding mechanisms. The 50% inhibitory concentration (IC50) of the quercitrin and afzelin were 0.231±0.033 mg/mL and 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The values of horizontal axis (−1/ K m ) remained unaltered and the values of vertical axis (1/ V max ) increased with increasing the concentrations of the detected compounds, which indicated that all the three compounds caused a non‐competitive inhibition. Other flavonols such as kaempferol, quercetin 3‐ O ‐(3′′‐ O ‐galloyl)‐ β ‐galactopyranoside, quercetin 3‐ O ‐(6′′‐ O ‐galloyl)‐ β ‐glucopyranoside, quercetin 3‐ O ‐ β ‐glucopyranoside and quercetin 3‐ O ‐ β ‐galactopyranoside also demonstrated non‐competitive inhibition [5,19,21] . For non‐competitive inhibition, inhibitors bind to other site of the enzyme‐substrate complex instead of competing with pNPG for active sites.…”
Section: Resultsmentioning
confidence: 99%
“…The values of horizontal axis (−1/ K m ) remained unaltered and the values of vertical axis (1/ V max ) increased with increasing the concentrations of the detected compounds, which indicated that all the three compounds caused a non‐competitive inhibition. Other flavonols such as kaempferol, quercetin 3‐ O ‐(3′′‐ O ‐galloyl)‐ β ‐galactopyranoside, quercetin 3‐ O ‐(6′′‐ O ‐galloyl)‐ β ‐glucopyranoside, quercetin 3‐ O ‐ β ‐glucopyranoside and quercetin 3‐ O ‐ β ‐galactopyranoside also demonstrated non‐competitive inhibition [5,19,21] . For non‐competitive inhibition, inhibitors bind to other site of the enzyme‐substrate complex instead of competing with pNPG for active sites.…”
Section: Resultsmentioning
confidence: 99%
“…The flavonoid heteroside quercitrin (quercetin-3-O-ramnoside) ( 94 ) was isolated from S. rebaudiana as documented in the Stevia genus [ 1 ]. The biological activity of this compound has been extensively studied through the years, involving anti-inflammatory activity determined by Camuesco et al [ 235 ], antiproliferative and proapoptotic effects by Cincin et al [ 236 ], anti-Dengue virus 2 [ 237 ], osteoporosis attenuation [ 238 ], hair growth stimulation [ 239 ], improvement of hyperlipidemia and hepatic steatosis in ovariectomized mice [ 240 ], and inhibition of α-glicosidase [ 241 ]. Like other flavonoids discussed in this update, quercitrin was reviewed by Boniface and Ferreira et al [ 176 ], showing antiprotozoal activity against P. falciparum (43.4% inhibition after 48 h), inhibitory effects on L. amazonensis arginase (IC 50 = 10.0 µM), and activity against Dengue virus 2 (DENV-2 NS2B) (IC 50 = 43.6 µM) and Dengue virus 3 (DENV-3 NS2B) (IC 50 = 32.0 µM).…”
Section: Biological Activitymentioning
confidence: 99%
“…Killick leaves [55] Methanol extract of Myrica gale L. seeds [54] Cryptostrobin (31) Dichloromethane extract of Morella serrata (Lam.) Killick leaves [55] Demethoximatteucinol-7methoxy (32) Methanol extract of Myrica gale L. seeds [54] Methanol extract of Myrica gale L. seeds [54] Gallocatechin-4-α-8epicatechin (34) Aerial parts of Myrica gale L. [80] Gallocatechin-4-α-8epigallocatechin (35) Aerial parts of Myrica gale L. [80] Adenodimerin B (36) Methanol extract of Morella adenophora (Hance) J. Herb. roots [19] Adenodimerin C (37) Methanol extract of Morella adenophora (Hance) J. Herb.…”
Section: Other Phytochemicals Identified In Morella and Myrica Speciesmentioning
confidence: 99%
“…roots [19] Adenodimerin C (37) Methanol extract of Morella adenophora (Hance) J. Herb. roots [19] Methanol extract of Myrica gale L. (Myrica gale var tormentosa L.) branches [24] Gallocatechin-4-α-8-epicatechin (34) Gallocatechin-4-α-8epicatechin (34) Aerial parts of Myrica gale L. [80] Gallocatechin-4-α-8epigallocatechin (35) Aerial parts of Myrica gale L. [80] Adenodimerin B (36) Methanol extract of Morella adenophora (Hance) J. Herb. roots [19] Adenodimerin C (37) Methanol extract of Morella adenophora (Hance) J. Herb.…”
Section: Other Phytochemicals Identified In Morella and Myrica Speciesmentioning
confidence: 99%
See 1 more Smart Citation